2016
DOI: 10.1002/fsn3.429
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage temperature and low‐temperature conditioning on the levels of health‐promoting compounds in Rio Red grapefruit

Abstract: Commercial operations use low‐temperature conditioning of citrus fruits to reduce the incidence of chilling injury (CI) during cold storage and quarantine treatments. Rio Red grapefruits (Citrus paradisi Macf) were stored for 12 weeks at 11°C or 5°C; an additional set was temperature conditioned at 16°C for 7 days before storing at 5°C (CD). Every 3 weeks, samples were assessed for chilling injury (CI) and health‐promoting compounds such as ascorbic acid, carotenoids, limonoids, flavonoids, and furocoumarins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
2
17
0
1
Order By: Relevance
“…However, studies on carotenoids in the edible juice sacs of the fruit have been limited and conducted for only a few cultivars and storage conditions. Recent studies have reported that in the pulp of grapefruit and oranges, the carotenoid content in fruit stored at 11-20°C was higher than that in fruit stored below 5°C (Carmona et al, 2012;Chaudhary et al, 2012Chaudhary et al, , 2014Chaudhary et al, , 2017. Previously, we reported that in 'Aoshima' satsuma mandarin fruit harvested at the fully-colored stage, the carotenoid content in the juice sacs did not change notably during storage at 5 or 20°C for three weeks (Matsumoto et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, studies on carotenoids in the edible juice sacs of the fruit have been limited and conducted for only a few cultivars and storage conditions. Recent studies have reported that in the pulp of grapefruit and oranges, the carotenoid content in fruit stored at 11-20°C was higher than that in fruit stored below 5°C (Carmona et al, 2012;Chaudhary et al, 2012Chaudhary et al, , 2014Chaudhary et al, , 2017. Previously, we reported that in 'Aoshima' satsuma mandarin fruit harvested at the fully-colored stage, the carotenoid content in the juice sacs did not change notably during storage at 5 or 20°C for three weeks (Matsumoto et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…These results suggest that the effects of temperature on the accumulation of β-cryptoxanthin in the juice sacs was maturation stage-dependent and that the accumulation on the tree would continue in postharvest fruit at 20°C, but not at 5°C, for at least 15 days after harvest. Recent studies have shown that storage temperature affect the carotenoid content in the pulp of several citrus varieties, and the higher content during storage tended to be maintained at 10-20°C compared to below 5°C (Carmona et al, 2012;Chaudhary et al, 2012Chaudhary et al, , 2014Chaudhary et al, , 2017Matsumoto et al, 2009). In satsuma mandarin fruit harvested in early December, we previously reported that the carotenoid content in the juice sacs did not clearly increase at 20°C, but the content was higher at 20°C than at 5°C for three weeks (Matsumoto et al, 2009).…”
Section: Experiments 1: the Effect Of Temperature And Maturation Stagementioning
confidence: 84%
See 1 more Smart Citation
“…Os teores variaram de 11,59 a 12,80%, no presente estudo. Comportamento similar foi relatado por Chaudhary et al (2016), analisando frutos de citros da cultivar Rio Red (Citrus paradisi Macf), cujos valores se mantiveram constantes durante 12 dias a 5 °C. Nascimento et al (2011), ao avaliarem tangerinas W Murcott armazenadas em ambiente refrigerado por 90 dias, encontraram teores similares (11,65%) aos obtidos neste estudo.…”
Section: Experimento 2: Métodos De Sanificação E De Eliminação Do Excunclassified
“…Moreover, these symptoms may appear during storage, immediately after the cold storage or after several days of being exposed to room temperature (Hashim et al., ). CI causes degradation of carotenoids, reduced flavor and aroma level, and breakdown of flesh and tissue (Cantre et al., ; Chaudhary, Yu, Jayaprakasha, & Patil, ; Zhang et al., ). This condition makes mango easily susceptible to fungal decay that may attract other further infections, thereby reducing shelf life and commercial value.…”
Section: Introductionmentioning
confidence: 99%